2015
DOI: 10.1016/j.ijsu.2015.04.094
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pancreatectomy: Did the indications change? A review from literature

Abstract: Pancreatic Cancer (PC) is the fourth cause of death for tumors in Western countries. Symptoms are not specific, and can vary according to the tumor size and place. Diagnostic workup includes CA 19-9, CT and MRI. Surgery is the only treatment for PC, associated to radio-chemo therapy. Laparoscopic approaches are actually used for PC treatment in few specialized centers, and could be an alternative to laparotomic surgery. The aim of our study is to evaluate the efficacy of laparoscopy for PC treatment compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…En cuanto a las complicaciones posquirúrgicas, la fuga pancreática y la formación de fístulas son las que se reportan con mayor frecuencia. También, se han registrado abscesos pancreáticos, seudoquistes, retardo en el vaciamiento gástrico, obstrucción intestinal, colitis seudomembranosa, colangitis, neumonitis e infección del sitio operatorio, con reportes variables de morbilidad perioperatoria (rango de 0 a 62 %) 5,36,38,40 .…”
Section: Discussionunclassified
“…En cuanto a las complicaciones posquirúrgicas, la fuga pancreática y la formación de fístulas son las que se reportan con mayor frecuencia. También, se han registrado abscesos pancreáticos, seudoquistes, retardo en el vaciamiento gástrico, obstrucción intestinal, colitis seudomembranosa, colangitis, neumonitis e infección del sitio operatorio, con reportes variables de morbilidad perioperatoria (rango de 0 a 62 %) 5,36,38,40 .…”
Section: Discussionunclassified
“…Many researchers have written systematic reviews of laparoscopic DP, and these reviews and institutional series described outcome parameters [ 76 80 ]. Many surgeons suggested that laparoscopic DP is safe and reasonable [ 76 80 ], though only few reports of laparoscopic DP for SPN were reported [ 6 8 ]. Laparoscopic DP with or without splenic preservation is beneficial for curative treatment of SPN if surgical procedures are carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic pancreatic surgery began with resection of small and benign lesions (enucleation) and progressed to caudal, total, central and duodenal pancreatectomy procedures 3 , 11 , 12 , 19 . Despite all the technical difficulties inherent to pancreatic surgery, laparoscopic distal pancreatectomy has been gradually included in the routine of various services because their results are similar to those from laparotomy, including in cases of malignant disease 8 , 18 .…”
Section: Introductionmentioning
confidence: 99%